(untitled) (Medico Legal Update, 2020)
Background: The role of type I collagen is as a matrix of extracellular proteins with characteristics of increased cell proliferation which directly affects the physiology and morphology of cells. Type 1 collagen can be obtained from fish scales. Thus, this research aimed to support engineering tissue used for the treatment of periodontal disease in the regenerative surgery by utilizing collagen derived from gouramy scales. As an initial step, the researchers wanted to conduct a study used collagen extract derived from gouramy scales (Osphoronemusgouramy) which was applied to bone marrow mesenchymal stem cell cultures to see viability in vitro. Objective: To determine the viability of collagen from fish scales (Osphronemusgouramy) to bone marrow mesenchymal stem cells. Method: Bone marrow mesenchymal stem cells are taken from mice and planted in 96 well plates. Collagen extracted from gouramy scales using the enzymatic method was dissolved in a condition medium with each concentration of 0.01 mg/ml, 0.02 mg/ml, 0.04 mg/ml, 0.16 mg/ml, 0.32 mg/ ml was put into the well prepared and incubated for 24 hours for the MTT assay. Result: Collagen from fish scales can increase the viability of bone marrow mesenchymal stem cells with a percentage above 90% and the highest viability concentration at 0,01 mg/ml. Conclusion: Collagen from fish scales is viable against bone marrow mesenchymal stem cells. Collagen scales of gouramy soaked in medium had the highest viability with an optimum dose of 0.01 mg/ml.